The contributions of the community schools of Urdaneta to rural development and its implication for teacher education in the Republic of Vietnam - Doanh, Pham 1938- (s.n.], 1971)
This study was designed to present, analyze and assess some activities of the community schools of Urdaneta in rural development particularly in four areas of living, namely: health and sanitation, literacy, citizenship development, and economic growth. The method of research used was the descriptive analysis type with interview, observation, and opinionnaire as tools for gathering data. The data showed that the community schools of Urdaneta have contributed little in the development of the four areas of living. In these four areas, they have contributed most to health and sanitation, and least in economic growth.